A Proposed Cultural Edutourism Framework for Local Tradition Preservation under Merdeka Belajar - Protasius Jehane; Chistina Welly Plaituka; I Wayan Adi Putra Ariawan (Goodwood Publishing, 2026)
Purpose: This study aims to analyze the potential of culture-based edutourism as a learning medium in formal education to support local culture preservation amid globalization. Research Methodology: This research employs a descriptive qualitative approach with explorative properties, conducted specifically in Kupang City, East Nusa Tenggara. Data were collected through comprehensive literature studies and in-depth interviews with educators, tourism business actors, and other relevant parties. Results: The results show that culture-based edutourism has the potential to be an effective learning medium through direct-field experience. Integration can be achieved through curriculum synchronization, active teacher roles and strategic collaboration with tourism operators. However, implementing this concept faces challenges, such as limited stakeholder understanding, educational institutional readiness, and government policy support. Conclusions: This study concludes that culture-based edutourism has strategic opportunities as a contextual learning approach that supports sustainable local culture preservation. Limitations: The limitation of this study is its initial conceptual nature, requiring further empirical testing, such as classroom action research, to measure effectiveness. Contributions: This research provides a model for integrating the formal curriculum with the tourism industry for educators, the government, and tour operators in national tradition preservation efforts.